Talent Management Practices in Institutions of Higher Learning: Impact of Recruitment and Culture on Employee Performance in Adamawa State Nigeria (Global Journal of Human-Social Science, 2020)
Abstract not found
Keywords: talent management practices; employee performance; adamawa state